Foam sclerotherapy combined with saphenofemoral ligation procedure: long-term results - Soylu, Lütfi; Aydın, Oğuz Uğur (The European Research Journal, 2019)
Objective: To evaluate the clinical effect of the foam sclerotherapy combined with saphenofemoral ligation (FS-SFL) in a selected group of patients with varicose disease and present the long-term results of ten-year ultrasonographic follow-up. Methods: Sixty-five patients with primary varicose veins due to the great saphenous vein incompetence who had been treated with FS-SFL were retrospectively reviewed over a period of ten years. The patients were assessed before and after the treatment by Doppler ultrasonography and clinical examination. Results: The mean age of the patients was 44.6 ± 11 years (range: 19 to 87 years), and 51 were females and 14 were males. Follow-up for all patients was ten years. The most common complication was skin pigmentation. There were no major complications. No recanalization of the great saphenous vein was seen in any patient. Conclusions: FS-SFL is a safe and effective method of treating varicose veins. This treatment have a low rate of recanalization in their long-term follow-up.